2014
DOI: 10.3238/arztebl.2014.0592
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Therapy in Hip Osteoarthritis

Abstract: Twelve weeks of exercise therapy in hip osteoarthritis patients of normal vitality reduced pain and improved physical function. No significant improvement was found in these patients' general health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 18 publications
1
55
2
2
Order By: Relevance
“…These results were consistent with the results of other studies (19,20), although one study observed lower scores in the SF-36 RP domain after rehabilitation (23). The SF-36 RS domain showed the largest improvement after rehabilitation; this finding contradicted the results observed in other studies (14,19,23), with some studies reporting high scores for that domain before rehabilitation (1,12). Generally, hip OA patients receive low scores for the SF-36 BP domain (1,12,14,15,(19)(20)(21)(22)(23)(24), which was in accordance with our results; thus, after rehabilitation, this was one of the domains that showed moderate improvement in our patients, although other studies reported that this domain showed the greatest improvement (14-16, 20, 23, 25).…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…These results were consistent with the results of other studies (19,20), although one study observed lower scores in the SF-36 RP domain after rehabilitation (23). The SF-36 RS domain showed the largest improvement after rehabilitation; this finding contradicted the results observed in other studies (14,19,23), with some studies reporting high scores for that domain before rehabilitation (1,12). Generally, hip OA patients receive low scores for the SF-36 BP domain (1,12,14,15,(19)(20)(21)(22)(23)(24), which was in accordance with our results; thus, after rehabilitation, this was one of the domains that showed moderate improvement in our patients, although other studies reported that this domain showed the greatest improvement (14-16, 20, 23, 25).…”
Section: Resultscontrasting
confidence: 60%
“…Hip osteoarthritis (OA) is a degenerative, progressive musculoskeletal system disease in adult individuals (1). It is firstly characterized by both progressive articular cartilage loss (2,3) and appositional new bone formation in the subchondral trabeculae at the joint margins (osteophytes) (3).…”
Section: Introductionmentioning
confidence: 99%
“…Second, one recent trial on exercise therapy in patients with hip osteoarthritis demonstrated the superiority of exercises in comparison to sham treatment, illustrating the potential additional benefit of active treatment versus placebo 5. This finding is in contrast to the presented results of the active physical therapy programme, raising the question about its effective dose–response relationship.…”
Section: Commentarymentioning
confidence: 87%
“…Based on some studies and the 2014 Cochrane database, there is evidence that in hip osteoarthritis, exercise decreases joint pain and improves function (Tak et al 2005;Fransen et al 2014;Krauß et al 2014); however, in a recently published, placebo-controlled study, no difference in pain was found between exercise therapy and placebo (Bennell et al 2014).…”
Section: Introductionmentioning
confidence: 95%